CRISPR/Cas9 establishment-mediated targeted mutagenesis in Macrobrachium nipponense - Qiao, Hui; Jiang, Sufei; Fu, Hongtuo; Xiong, Yiwei; Zhang, Wenyi; Xu, Lei; Cheng, Dan; Wang, Jisheng (Frontiers in Physiology, 2023)
CRISPR/Cas9 is a gene-editing technology which could specifically cleave dsDNA and induces target gene mutation. It has been widely used in gene functional studies in many fields such as medicine, biology and agriculture due to its advantages of simple design, low cost and high efficiency. Although it has been well developed in model fish and freshwater fish for gene function analysis, it was still novel in studies in economic crustacean species. In this study, we established a CRISPR/Cas9 system based on microinjection for Macrobrachium nipponense, an important economic crustacean aquaculture species. Vitellogenin (Vg) gene and the Eyeless (Ey) gene were selected as the targeted genes for mutation. Two sgRNAs were designed for Mn-Vg and Mn-Ey gene editing, respectively. For sg-Vg-1, the gastrula survival ratio was 8.69% and the final hatching ratio was 4.83%. The blastula mutant ratio was 10% and hatching individual mutant ratio was 30%. For sg-Vg-2, the gastrula survival ratio was 5.85% and the final hatching ratio was 3.89%. The blastula mutant ratio was 16.67% and No mutant sequences were detected in hatching individuals. For sg-Ey-1, the gastrula survival ratio was 6.25% (8) and the final hatching ratio was 2.34%. The blastula mutant ratio was 10.00% and hatching individual mutant ratio was 66.67%. For sg-Ey-2, the gastrula survival ratio was 6.00% (9) and the final hatching ratio was 2.67%. No mutant sequence was detected in both blastula stage and hatching individuals. There were no significant morphological changes were observed in Mn-Vg group. Two deformed types were detected in sg-Ey-1 injected-embryos. An obvious developmental delay of compound eye was detected in Ey-sg1-H1in zoea stage. The compound eyes of Ey-sg1-H2 embryo could not form well-defined spheres and the whole compound eyes appeared diffuse at the end of late zoea stage. The establishment of gene editing platform based on CRISPR/Cas9 will not only provide an efficient and convenient method for gene function analysis, but also provide a powerful tool for molecular assisted breeding of M. nipponense.